Management of Zakat Infaq Sadaqah to Overcome Poverty and The Impact of Emergency Situations - Murni Murni; Indah Purbasari; Faris Hamidi (International Journal of Islamic Thought and Humanities, 2023)
The stipulation of COVID-19 as a global pandemic affects all aspects of human life in the world. To deal with the pandemic spread, the Indonesian Government chose not to do a lockdown (quarantine), but instead to carry out social distancing and physical distancing until the issuance of Government Regulation (PP) of the Republic of Indonesia Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB). The restrictive policy had an impact on the employment sector and the poverty rate increases. ZIS potential in tackling poverty can be a solution, during the Covid 19 pandemic there were problems, namely das sollen (law in book) and das sein (law in action) problems faced, namely whether the withdrawal and distribution of ZIS been carried out according to health protocols and has the management of ZIS during the pandemic followed Sharia rules. The research used socio-legal research which combined the norms and the application in society. The results showed that although the management of ZIS during the Covid 19 pandemic had met health protocol standards and compliance with the sharia rules, the potential for ZIS had not been able to overcome poverty, because the number of mustahik increased and the number of muzakki decreased so that the acquisition of ZIS funds was insufficient. Besides, the infaq and shodaqoh distributions still focused on human being poverty but lack of allocation for other creature needs and environmental impact.